Tinjauan Kritis Pemberlakuan Restorative Justice dalam Sistem Peradilan Pidana Kasus Perkosaan Anak di Indonesia - Novi Enjelina Putri; Annisa Firdhausy; Rizaldy, Wahyu Fahmi (Universitas Teknologi Surabaya, 2025)
Restorative justice, originally designed to protect the future of the offender's child, in practice creates new inequalities by failing to ensure justice and protection for victims, particularly in the context of sexual crimes with severe physical and psychological consequences. This research emphasizes the need to critically evaluate the application of restorative justice in child rape cases, so that it does not become a shortcut to solving cases without comprehensively considering the rights of victims and the principles of substantive justice. This research criticizes the application of restorative justice in the juvenile criminal justice system, particularly in rape cases involving children as both perpetrators and victims. Using a normative legal approach, this research analyzes how restorative justice is prioritized as a form of peaceful resolution, but may ignore the rights and overall recovery of victims.